2022
DOI: 10.1002/ajpa.24603
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the extent human milk folate is buffered against maternal malnutrition and infection in drought‐stricken northern Kenya

Abstract: Objectives: Folate is an essential nutrient fundamental to human growth and development. Human milk maintains high folate content across the maternal folate status range, suggesting buffering of milk folate with prioritized delivery to milk at the expense of maternal depletion. We investigated whether and how the extent of this buffering may diminish under prolonged nutritional and/or disease stress, while taking into consideration infants' varying vulnerability to malnutrition-related morbidity/ mortality. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…In fact, several studies have shown a relationship between hypohomocysteinemia and cardiovascular disease fatalities in addition to hyperhomocysteinemia. The strong correlation between homocysteine and inflammatory indicators of malnutrition may be the cause of these contradicting observations [29].…”
Section: High Homocysteine Levelsmentioning
confidence: 99%
“…In fact, several studies have shown a relationship between hypohomocysteinemia and cardiovascular disease fatalities in addition to hyperhomocysteinemia. The strong correlation between homocysteine and inflammatory indicators of malnutrition may be the cause of these contradicting observations [29].…”
Section: High Homocysteine Levelsmentioning
confidence: 99%
“…A secondary analysis was conducted using data from a cross-sectional survey of breastfeeding mother-infant dyads in the Ariaal agropastoral communities of northern Kenya (Fujita et al, 2022). This population relies heavily on the rearing of mixed-species livestock and small-scale dryland farming for subsistence and cash cropping (Fratkin, 2019).…”
Section: Study Populationmentioning
confidence: 99%
“…(Ross & Desai, 2005) How does drought affect biomarkers of inflammation, immune function, methylation, and disease? (Fujita et al, 2022;Straight et al, 2022) Wildfires How do wildfires affect pulmonary function? How do wildfires affect stress and cognitive performance?…”
Section: Extreme Heat/ Heatwavesmentioning
confidence: 99%